Pengembangan Lembar Kerja Siswa (LKS) Menulis Proposal Karya Ilmiah Berbasis Kontekstual Siswa Kelas XI SMA Negeri 1 Lubuklinggau - Sumariani Sumariani; Satinem Satinem; Juwati Juwati (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
Student worksheets (LKS) so far are still textual so students still have difficulty understanding the contents of the text they learn. For this reason, contextual worksheets are needed so that students are expected to understand the material and assignments they will be doing because students have initial concepts about the text to be read. This study aims to produce worksheets on writing material for scientific work proposals based on contextual grade XI students of SMA Negeri 1 Lubuklinggau. This research is a type of research development or Research and Development (R&D). Data collection techniques in this study were interviews, questionnaires, and tests. While the data analysis techniques in this study are the validity test and reliability test using SPSS version 20. The results of the study show that the Worksheet for Writing Contextual Scientific Work Proposals is effective in increasing students' learning abilities so that they can be used as teaching materials in schools. This is evidenced by the validity of LKS writing contextual-based scientific work proposals classified in the good category with a percentage of 79.80%. Furthermore, the practicality of LKS gained 85.4% with a very positive category. The effectiveness of LKS writing scientific paper proposals seen from the average post-test score is better than the pre-test average value of 81.52 greater than 57.45. Based on the results of the paired samples test output the average value before and after was 24.06 with Sig (2-tailed) of 0.00 (smaller than the alpha value). Thus, there are significant differences between before and after using LKS writing contextual based scientific work proposals.